PENGARUH LIKUIDITAS TERHADAP PERUBAHAN LABA PADA PT. BANK SUMUT - DESYANA PUTRI; KARINA SILAEN; AMRIL . (LP2MTBM MAKARIOZ, 2022)
This research aims to test whether the liquidity ratio of Loan to Deposit Ratio (LDR) and Cash Ratio (CR) affects changes inprofit at PT. Bank Of North Sumatra period 2005-2011. The data analysis techniques used are descriptive statistics, multiplelinear regressions and hypothesis tests that use t- statistics to test partial regression coefficients as well as F - statistics totest the meaning of influence together - equal to a significant rate of 0.05 (5%). The results showed that partially thevariables loan to deposit ratio (LDR) and cash ratio (CR) had no effect and no significant effect on the change in profit at PT.Bank Sumut period 2005 - 2011 because t table is greater than t calculated with a significance value level of less than 5%.Simultaneous testing shows that all independent variables namely Loan to Deposit Ratio (LDR) and Cash Ratio (CR) haveno effect and are insignificant to the change in profit because F table is greater than F calculated with a significance valuelevel of less than 5%. Then the predictive ability of the two variables to the change in profit of 14.7%, while the remaining85.3% was influenced by other factors that were not included in the research model.